Study on the Damage Diagnosis of Ancient Wood Structure in Tianshui under Traffic Excitation - Xin Wang; Zhaobo Meng; Xicheng Zhang (Advances in Civil Engineering)
Three-dimensional finite element model of the wood structure-foundation of the North House’s main hall in Tianshui under ground traffic excitation was established, and the damage of the first-floor longitudinal beam of the wood structure was simulated by the finite element method. The node acceleration response signals on beams were decomposed with a wavelet packet. The wavelet packet energy curvature difference index was proposed to determine the structural damage location. The results show that the wavelet packet energy curvature difference can decide the damage location of the middle part of the first-floor longitudinal beam, and the index value increases with the increase of damage degree. If SNR is 40 db or larger, the damage index can accurately identify the damage of ancient wooden structures. When SNR increases, the damage index will have an increasingly higher sensitivity and certain ability to resist the effect of noise. The function relation between the damage index and the damage degree is obtained to determine the structural damage degree. The study results provide a theoretical basis for the damage diagnosis of the wood structure of ancient buildings along the traffic line.